Freeze and microwave vacuum combination drying technique for sea cucumber - Qian, Zhang; Guochen, Zhang; Gang, Mu; Yue, Liu (International Journal of Agricultural and Biological Engineering, 2012)
To improve the quality and efficiency of sea cucumber drying, an orthogonal experiment of freeze and microwave vacuum combination drying technique was carried out. Factors and levels were FD time of conversion point (8 h, 16 h and 24 h), initial microwave power density (1.7 W/g, 2.0 W/g and 2.3 W/g) and microwave intermittent ratio (12s-on/18s-off, 14s-on/16s-off and 20s-on/10s-off). Results showed that the optimal parameters of FD-MVD were 8 h FD conversion point, 1.7 W/g initial microwave power density, 12 s-on/18 s-off microwave intermittent ratio, and the maximum rehydration rate of 280.71%, the lowest shrinkage rate of 14.48%, the least drying time of 9.25 h and energy consumption of 77 316 kJ could be obtained. Keywords: sea cucumber, freeze drying, microwave vacuum, drying, combination DOI: 10.3965/j.ijabe.20120503.0010 Citation: Zhang Q, Zhang G C, Mu G, Liu Y. Freeze and microwave vacuum combination drying technique for sea cucumber. Int J Agric & Biol Eng, 2012; 5(3): 83